2018
DOI: 10.1002/ejic.201701344
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium p‐Cymene Iminophosphonamide Complexes: Activation under Basic Conditions and Transfer Hydrogenation Catalysis

Abstract: Complex [(η 6 -Cym)RuCl(NPN)] {Cym = p-cymene; NPN = (pTolN) 2 PPh 2 } (1) yields a thermally sensitive hydride derivative [(η 6 -Cym)RuH(NPN)] (2) by reaction with iPrOH in the presence of a strong base, via an observable isopropoxide intermediate [(η 6 -Cym)Ru(OiPr)(NPN)] (3), or with NaBHEt 3 in toluene. Partial conversion also occurs in iPrOH in the absence of base. 2 is stabilized by dihydrogen bonding with isopropyl alcohol, but attempts to isolate it induce isomerization by hydride migration to a ring C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…However, the chemistry of transition metal iminophosphonamides (NPN) that had been considered to be heteratomic analogs of the corresponding metal amidinates has been developing slowly. Nevertheless, in the last two decades transition metal iminophosphonamides have been reported as active catalysts for alkene polymerization (NiNPN, ZrNPN), 3,4‐selective polymerization of isoprene (rare earth NPN complexes), alkene oligomerization (CrNPN), ethene dimerization (NiNPN),[5c] cyclopropanation and aziridination (CuNPN), as well as for Tsuji–Trost cross‐coupling (PdN 2 P) Recently we have demonstrated that arene ruthenium iminophosphonamide [( p ‐cymene)RuCl{Ph 2 P(N‐ p Tol) 2 }] can efficiently reduce acetophenone under transfer hydrogenation conditions …”
Section: Introductionmentioning
confidence: 99%
“…However, the chemistry of transition metal iminophosphonamides (NPN) that had been considered to be heteratomic analogs of the corresponding metal amidinates has been developing slowly. Nevertheless, in the last two decades transition metal iminophosphonamides have been reported as active catalysts for alkene polymerization (NiNPN, ZrNPN), 3,4‐selective polymerization of isoprene (rare earth NPN complexes), alkene oligomerization (CrNPN), ethene dimerization (NiNPN),[5c] cyclopropanation and aziridination (CuNPN), as well as for Tsuji–Trost cross‐coupling (PdN 2 P) Recently we have demonstrated that arene ruthenium iminophosphonamide [( p ‐cymene)RuCl{Ph 2 P(N‐ p Tol) 2 }] can efficiently reduce acetophenone under transfer hydrogenation conditions …”
Section: Introductionmentioning
confidence: 99%
“…Complex 2c can alternatively be obtained by reacting 1c with 1 equiv. of NaBHEt3 in benzene-d6 (Figure S9a), 25 presenting the same characteristic resonances at δ 49.8 in 31 P NMR and at δ -4.09 in 1 H NMR (Figure S9b). Thus the hydride complex 2c is indeed generated in the reaction of 1c with isopropoxide, however due to the highly basic Natoms 27 it has very low stability in the presence of isopropanol, perhaps because of its facile protonation and further P-N bond alcoholysis to form the aminophosphine oxide.…”
Section: (B) Generation and Stability Of [(Arene)ru(npn)h] Speciesmentioning
confidence: 82%
“…We have recently described the generation of a hydride complex [(p-Cymene)RuH(NPN)] (2f, NPN = Ph2P(N-p-Tol)2) from the corresponding chloride 1f and sodium isopropoxide via β-H elimination in the isopropoxide intermediate [(p-Cymene)Ru(O i Pr)(NPN)] (3f). 25 Here we show that this procedure is operational for the generation of a wider array of ruthenium hydrides [(Arene)RuH(NPN)] (2a-e) from the corresponding chloride complexes 1a-e, although the stability of the products is very different.…”
Section: (B) Generation and Stability Of [(Arene)ru(npn)h] Speciesmentioning
confidence: 90%
See 1 more Smart Citation
“…The latter have been reported as active catalysts for alkene polymerization, 2 3,4-selective polymerization of isoprene, 3 alkene oligomerization, 4 ethene dimerization, 2c cyclopropanation, 5 and aziridination, 6 as well as for Tsuji-Trost cross-coupling 7 and acetophenone transfer hydrogenation. 8 Nonsymmetric iminophosphonamines bearing different N,N′-substituents have been efficiently utilized in the Kumada cross-coupling of aryl Grignard reagents with aryl chlorides and fluorides 9 and in controlling regio-and stereoselectivity in the polymerization of isoprene. 10 Generally, there are two major approaches to the synthesis of iminophosphonamines, i.e.…”
Section: Isolated Yields 58-80% In One Potmentioning
confidence: 99%